Bank Ownership and Performance in the Middle East and North Africa Region - Farazi, Subika; Feyen, Erik; Rocha, Roberto (2012)
Although both domestic and foreign private banks have gained ground in MENA in recent years, state banks continue to play an important role in many countries. Using a MENA bank-level panel dataset for the period 2001-08, the paper contributes to the empirical literature by documenting recent ownership trends and assessing the role of ownership and bank performance in MENA while accounting for key bank characteristics such as size and balance sheet composition. The paper analyzes headline performance indicators as well as their key drivers and finds that state banks exhibit significantly weaker performance, despite their larger size. This result is mainly driven by a larger holding of government securities, higher costs due to larger staffing numbers, and larger loan loss provisions reflecting weaker asset quality. The results reflect both operational inefficiencies and policy mandates. The paper also provides a detailed performance analysis of foreign and listed banks. Foreign banks are fairly new in MENA, yet perform on par with domestic banks despite their smaller size and higher investment costs. Listed banks exhibit superior performance driven by higher interest margins even in the face of higher costs associated with listing. Taken together, the results do not reject the development role for state banks, but do show that their intervention comes at a cost. As such, there is scope to reduce the share of state banks in some countries and to clarify the mandates, improve the governance, and strengthen the operational efficiency of most state banks in MENA.